Total Phenolic Content and Antioxidant Activity of Germinated Black Rice Variety Krisna Extract, Indonesia - Pasaribu, Sudana Fatahillah; Wiboworini, Budiyanti; Kartikasari, Lilik Retna (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: Indonesia is an agricultural country and the third-largest rice producer in the world. Pigmented rice tends to contain a lot of nutrients and bioactive compounds, namely phenols, anthocyanins, fiber, amino acids, tocopherols, and γ-oryzanol, and has antioxidant properties. Phenols are bioactive compounds and antioxidants which are beneficial for health. Since the synthetic antioxidants have carcinogenic properties, natural antioxidants used in this study. One of the plants that have the potential to have antioxidant activity and phenol content is black rice variety krisna from Sleman district, DI Yogyakarta, Indonesia. The germination process in rice can theoretically increase its bioactive compounds, thereby increasing the potential for antioxidant activity. Objective: To analyze the antioxidant activity and total phenol content of the germinated black rice extract variety krisna in Sleman district, D.I. Yogyakarta, Indonesia. Materials and Methods: This type of research was quantitative with laboratory experimental methods. The research sample was germinated black rice of a variety krisna from Indonesia. The extraction method used maceration, the total phenol analysis method used the Folin- Ciocalteu method, and the antioxidant activity analysis used the DPPH-method Free Radical Scavenging Assay. Results and Discussion: The germinated black rice extract of varieties krisna Indonesian has a total phenol content of 2269 mg/g and antioxidant activity 71.05%. Conclusion: Germinated black rice extract of variety krisna Indonesian contains total phenol and antioxidant activity so that it has the potential to have health benefits. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 127-135